The Use of Quizlet for Vocabulary Learning: A Lesson from Innovative Application - Bayaksud, Najwa; Putu Dian Danayanti Degeng; Khairil Azwar Razali (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
As an essential element for effective communication, vocabulary knowledge plays a crucial role in language acquisition. With the increased importance of vocabulary learning, there is a new revolution called MALL (Mobile-Assisted Language learning). Several studies have looked into the possible advantages of Quizlet. However, they are mostly concentrated on the utilization of material that is already available and its consequences on the students’ motivation and receptive vocabulary acquisition. Comparatively, little research has been done on discussing the students’ perception in the use of the Quizlet application as a tool for vocabulary learning, especially in senior high school students Thus, this study aims to investigate student’s perception with different level of achievement about the use of Quizlet as a vocabulary-learning tool. The researcher used a descriptive qualitative method and interview as the instrument to get an in-depth understanding about student’s perception in the use of Quizlet. There were six students with different levels of achievement in the English course as the participants of the study. The researcher used thematic analysis to analyze the collected data. According to the findings, Quizlet is found to be a useful tool for improving vocabulary acquisition, and students' positive opinions are reinforced by its gamified elements and multimedia integration. As technology continues to shape the landscape of education, platforms like Quizlet stand as examples of how innovative applications can revolutionize the learning experience. However, the findings could be strengthened by conducting additional study with larger participant sizes, more diversified data collection methods, and longer follow-up periods.